KESIAPAN BELAJAR SISWA MTs RAMBATAN KABUPATEN TANAH DATAR - Nurlaili, Nurlaili (Batanang : Jurnal Psikologi, 2024)
This study aims to determine the learning readiness of MTs Rambatan students. This study uses a descriptive quantitative approach. The population in this study were 61 students at MTs Rambatan Tanah Datar Regency. In this study, researchers used a saturated sampling selection technique, namely all members of the population became research subjects. Data in this study were collected using a questionnaire in the form of a Likert scale consisting of five answer choices, namely always, often, sometimes, rarely, and never. The scale used is the learning readiness scale developed by Nadhli Muhammad Nur Syifa (2023) with a reliability coefficient of 0.853. Data analysis in this study used statistical analysis with the help of SPSS version 26 software. The results showed that students at MTs Rambatan Tanah Datar Regency had learning readiness which was in the medium category with a frequency of 44 students or 72.1%. Furthermore, the results of the statistical analysis also show that there are differences in learning readiness in male and female students which can be seen from the average statistics and variability statistics. With the results of the learning readiness study, MTs Rbatan students will support and have a positive impact on the teaching and learning process (PBM).Keywords: learning readiness, student, PBM, and school.┬á